Efficacy of cyclophosphamide in treating connective tissue disease-related interstitial lung diseases - Valeria Nucera; Elisabetta Gerratana; Manuela Giallanza; Laura La Corte; Donatella Sangari (BioExcel Publishing Ltd, 2021)
Interstitial lung diseases (ILDs) are some of the first and most serious complications of connective tissue diseases (CTDs). However, the pathogenesis of CTD-related ILDs (CTD-ILDs) is still unclear and their treatment often depends on functional and radiographic disease progression as well as on patient age and comorbidities. It can be difficult to manage CTD-ILDs due to their heterogeneous nature, the lack of robust therapeutic data, and the few well-defined outcome measures. This review focuses on cyclophosphamide due to its crucial role in the treatment of systemic sclerosis-related ILD, particularly in the case of patients with progressive ILD. This narrative review was performed using PubMed, Medline, and Cochrane Library databases to retrieve English language papers published between 2000 and April 2020 concerning the treatment of CTD-ILDs with cyclophosphamide.